(3abg GdYeQGf hCKQg Ydi GdYeGFQ GdOjfjI GdHGbjI HeOjfI aGS (B:s (3OQGSI CKQjI (B/s - (3,fgGd YGOd YHO GdUeO CMeO s; (3eMeO eMeO GdcMdGhis (2024)
(3JJfGhd gPg GdQSGdI OQGSI eOi JCKjQ GdCMcGe GdabgjI Ydi GdYeGFQ GdOjfjI GdHGbjI HeOjfI aGS OQGSI CKQjI eYeGQjI; hPdc ef NdGd ebOeI hJegjO hNeSI aUhd, jJfGhd GdaUd GdChd efgG(B: (3OQGSI dCge eUGOQ hCUhd hCMcGe abg GdYeQGf HGdEVGaI ddJYQja HfTCJg hCge eUWdMGJg, CeG GdaUd GdKGfj(B: (3ajJfGhd CKQ GdCMcGe GdabgjI Ydi YeQGf eOjfI aGS ef NdGd OQGSI VhGHW EYeGQ GdeOf GdESdGejI hGdYhGed GdeDKQI Ydi YeQGf eOjfI aGS, aVdkG Yf EdbGA GdVhA Ydi CKQ GdCMcGe GdabgjI Ydi JNWjW eOjfI aGS hJchjfgG, aj Mjf jJfGhd GdaUd GdKGdK(B: (3CKQ GdCMcGe GdabgjI Ydi YeGQI eSGLO eOjfI aGS ef NdGd OQGSI GNJjGQ ehGbY GdeSGLO hehGO GdHfGA ai VhA GdCMcGe GdabgjI, h CKQ GdCMcGe GdabgjI Ydi JNWjW eSGLO eOjfI aGS, hCKQ eQGYGI Mb GdWQjb hNW GdJfXje Ydi eNWGWGJ eSGLO eOjfI aGS, ceG JfGhd GdaUd GdQGHY(B: (3CKQ GdCMcGe GdabgjI Ydi YeGQI eOGQS hRhGjG eOjfI aGS hOhQ GdCMHGS ai MaX hUjGfI GdYeGFQ GdOjfjI HGdeOjfI, CeG GdaUd GdNGeS(B: (3ajJfGhd OQGSI CKQ GdCMcGe GdabgjI Ydi GdhMOGJ hGdYfGUQ GdeYeGQjI HYeGFQ eOjfI aGS ef NdGd OQGSI GdhMOGJ hGdYfGUQ GdeYeGQjI GdechfI ddYeGFQ GdOjfjI hbWY GdCKGK hGdedGMb GdeGFjI, MjK jCJi cd Pdc ai VhA GdCMcGe GdabgjI, Ke jdi Pdc GdNGJeI hGdJi JMJhi Ydi Cge GdfJGFL hGdJhUjGJ, Ke jdjgG KHJ HGdCTcGd hGddhMGJ, hjfJgi GdHMK HbGFeI GdeUGOQ hGdeQGLY GdJj GYJeOJ YdjgG GdHGMKI aj gPg GdQSGdI (B. s
This thesis addresses the study of the impact of jurisprudential rulings on the remaining religious structures in the city of Fez through an archaeological and architectural perspective. It consists of an introduction, a preface, and five chapters. The first chapter discusses the most important sources, origins, and rulings of urban jurisprudence, in addition to defining its emergence and key terminology. The second chapter examines the impact of jurisprudential rulings on the urban development of the city of Fez by studying the regulations for the reconstruction of Islamic cities and the factors influencing the urban development of Fez, as well as shedding light on the effect of jurisprudential rulings on the planning and formation of the city. The third chapter focuses on the impact of jurisprudential rulings on the architecture of mosques in Fez by studying the selection of mosque sites and building materials in light of these rulings, the impact of jurisprudential rulings on the planning of mosques in Fez, and the effect of considering the right of way and organizational lines on the layouts of mosques in the city. The fourth chapter discusses the impact of jurisprudential rulings on the architecture of schools and zawiyas in Fez and the role of waqf in preserving and maintaining the religious structures in the city. The fifth chapter studies the impact of jurisprudential rulings on the units and architectural elements of the structures in Fez by examining the architectural units and elements that make up the religious structures, as well as the furnishings and water-related annexes, all in light of the jurisprudential rulings. This is followed by a conclusion that includes the most important findings and recommendations, followed by an appendix with figures and illustrations, and the research concludes with a list of sources and references relied upon by the researcher in this thesis.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B381-401.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdeSGLOs; (3GdBKGQ GdGSdGejIs; (3eOjfI aGS s -- (3abg GdYeQGfs -- (3GdeSGLOs -- (3GdeOGQSs